Gait Rehabilitation Device in Central Nervous System Disease: A Review - Kazuya Kubo; Takanori Miyoshi; Akira Kanai; Kazuhiko Terashima (Journal of Robotics)
Central nervous system diseases cause the gait disorder. Early rehabilitation of a patient with central nervous system disease is shown to be benefit. However, early gait training is difficult because of muscular weakness and those elderly patients who lose of leg muscular power. In the patient's walking training, therapists assist the movement of patient's lower limbs and control the movement of patient's lower limbs. However the assistance for the movement of the lower limbs is a serious hard labor for therapists. Therefore, research into and development of various gait rehabilitation devices is currently underway to identify methods to alleviate the physical burden on therapists. In this paper, we introduced the about gait rehabilitation devices in central nervous system disease.